The Reality of Counseling Services Provided by the School Counselor for Gifted and Talented Students in the Jordanian Government School - Sohaila M. Banat; Soua'd M. Ghaith; Mouhamed Sayel Barahmeh (Sultan Qaboos University, 2013)
This study aimed to investigate the reality of counseling services provided by the school counselor for gifted and talented students in the Jordanian governmental school. Also, it aimed to know the effects of some demographic variables. The researchers developed a scale for the counseling services that consisted of 50 items. The instrument included: psychological, academic, vocational, familial, social, and cognitive aspects. It was administrated after checking it's appropriate reliability and validity. The sample consisted of 174 counselors from Salt, Zarqa, Almafraq, Alrosaifa, and Ain Albasha directories in Jordan. The results showed that the counselors practicing low level of the counseling services. Also, the results indicated a significant difference in the counseling services provided to gifted and talented students due to the years of the experience fevoring to the counselors with an experience less than five years. On the other hand, there were no significant differences due to gender, degree, type of school, and the number of the students. In light of these results the researchers recommended that training opportunities and enhanecement should be provided to the counselors who serve the gifted and talented students in public schools.